Investigation of AlyGa1−yN/Al0.5Ga0.5N quantum dot properties for the design of ultraviolet emitters. (6th April 2016) - Brault, Julien; Matta, Samuel; Ngo, Thi-Huong; Korytov, Maxim; Rosales, Daniel; Damilano, Benjamin; Leroux, Mathieu; Vennéguès, Philippe; Al Khalfioui, Mohamed; Courville, Aimeric; Tottereau, Olivier; Massies, Jean; et al.
Abstract: Self-assembled Al y Ga1− y N quantum dots (QDs), with y = 0 and 0.1, have been grown by molecular beam epitaxy on Al0.5 Ga0.5 N(0001) oriented layers using sapphire substrates. The QD formation has been followed in situ by reflection high energy electron diffraction (RHEED). A two- to three-dimensional (2D–3D) transition of the layer morphology is observed, characterized by a change of the RHEED pattern from streaky lines to Bragg spots. High QD densities, from 10 10 up to near 10 12 cm −2, have been obtained. By decreasing the GaN QD size and incorporating Al inside the QDs, a strong variation in the photoluminescence (PL) emission has been observed, enabling to cover a large spectral range from near UV (3 eV) to UV-B (3.95 eV). By combining temperature-dependent and time-resolved PL measurements, the internal quantum efficiency of the QDs has been determined at both low and high temperatures as a function of the PL energy.